Cobalt diselenide nanobelts grafted on carbon fiber felt: an efficient and robust 3D cathode for hydrogen production1. Issue 8 (14th August 2015) - Zheng, Ya-Rong; Gao, Min-Rui; Yu, Zi-You; Gao, Qiang; Gao, Huai-Ling; Yu, Shu-Hong
<x xml:space="preserve">Abstract</x> An easily scaled-up 3D CoSe2/CFF hierarchical electrode has been developed as a highly active and stable hydrogen evolution reaction cathode.